2021
DOI: 10.3389/fonc.2021.686044
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prognostic Model Based on Ferroptosis-Related Gene Signature for Bladder Cancer

Abstract: BackgroundBladder cancer (BC) is a molecular heterogeneous malignant tumor; the treatment strategies for advanced-stage patients were limited. Therefore, it is vital for improving the clinical outcome of BC patients to identify key biomarkers affecting prognosis. Ferroptosis is a newly discovered programmed cell death and plays a crucial role in the occurrence and progression of tumors. Ferroptosis-related genes (FRGs) can be promising candidate biomarkers in BC. The objective of our study was to construct a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…A high level of FANCD2 expression upregulated the immune inhibitor expression of CTLA4, PDCD1, and LAG3 while downregulating immunostimulators, such as IL6R, TMEM173, TNFSF13, CD40LG, and HHLA2, which indicates that FANCD2 contributes to tumor immune escape by modulating the immunosuppressive microenvironment. This finding is consistent with previous studies ( Hong et al, 2021 ; Yang et al, 2021 ). Moreover, higher FANCD2 expression led to a remarkable reduction in the infiltration of CD8 + T cells, NK cells, and DC cells, but it also recruited Th2 cells, and it is closely connected to the corresponding marker genes of tumor infiltrates immune cells (TIICs) based on the ssGSEA, CIBERSORT, and GEPIA databases.…”
Section: Discussionsupporting
confidence: 94%
“…A high level of FANCD2 expression upregulated the immune inhibitor expression of CTLA4, PDCD1, and LAG3 while downregulating immunostimulators, such as IL6R, TMEM173, TNFSF13, CD40LG, and HHLA2, which indicates that FANCD2 contributes to tumor immune escape by modulating the immunosuppressive microenvironment. This finding is consistent with previous studies ( Hong et al, 2021 ; Yang et al, 2021 ). Moreover, higher FANCD2 expression led to a remarkable reduction in the infiltration of CD8 + T cells, NK cells, and DC cells, but it also recruited Th2 cells, and it is closely connected to the corresponding marker genes of tumor infiltrates immune cells (TIICs) based on the ssGSEA, CIBERSORT, and GEPIA databases.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, FANCD2 plays an immunosuppressive role by downregulating immunostimulators, such asIL6R, TMEM173, TNFSF13, CD40LG, and HHLA2. Therefore, the results implied that FANCD2 contributes to tumor immune escape by modulating the immunosuppressive microenvironment, which was consistent with previous studies [35,36].…”
Section: Discussionsupporting
confidence: 92%
“…For example, a novel agent called AuNRs&IONs@Gel constructed by Pengyu Guo was reported to induce ferroptosis and trigger a potent immune response through a triple therapy strategy using FDA-approved nanoparticles in BLCA [ 39 ]. The relationship between immune statue and ferroptosis in BLCA has been explored by accumulating studies [ 40 , 41 ]. Luan et al found that immune cell infiltration and immune checkpoints in BLCA were dysregulated in BLCA patients with different levels of ferroptosis related genes using multiple experimental and bioinformatic models [ 41 ].…”
Section: Discussionmentioning
confidence: 99%